KISAH SEORANG PRAMURIA: MAKNA TUBUH, INTIMASI, DAN SEKSUALITAS PADA PEREMPUAN LADY COMPANION DI SURAKARTA - Silvani Adiningtyas; Rezza Dian Akbar (Jurnal Analisa Sosiologi, 2023)
This study aims to explore the social phenomena that occur in the nightlife, namely the Lady Companion phenomenon or commonly called karaoke guides which are closely related to the practice of prostitution. And what is the meaning of sexual relations and intimacy by LC women who are prostitutes and what is the meaning of the body and "women's chastity" to LC women who are prostitutes. At present the trend of prostitution practice has grown rapidly and has many kinds. One of them is in the world of Indonesian music entertainment, namely karaoke. The existence of a karaoke place cannot be separated from the presence of a woman who accompanies him to sing who is usually called a karaoke guide or better known as LC (Lady Companion). The initial fact of karaoke is seen as an activity that is identical with negative connotations. Even though formally they are not official or open actors of prostitution, in practice their profession is very close and identical to the practice of prostitution. The method used is qualitative research using an interpretative approach of "meaning" based on the views of Foucault and Giddens. The results of this study are that there is a relationship between the LC profession and the practice of prostitution with the female body as a means of production or making money and the existence of power over her that controls the urgent economic needs and finally LC women enter the world. Then there was a shift in social instructions regarding the meaning of the body and "women's chastity" because sexual relations and virginity were no longer considered sacred as before.Keywords: Lady Companion (LC), Prostitution, Body Meaning, Women's ChastityAbstrak Penelitian ini bertujuan untuk mengupas fenomena sosial yang terjadi di dunia malam yaitu fenomena Lady Companion atau biasa dipanggil pemandu karaoke yang kaitannya erat dengan praktik prostitusi. Dan bagaimana makna hubungan seksual dan intimasi yang dilakukan perempuan LC pelaku prostitusi serta bagaimana makna tubuh dan "kesucian perempuan" pada perempuan LC pelaku prostitusi. Pada masa sekarang trend praktik prostitusi telah berkembang pesat dan banyak macamnya. Salah satunya pada dunia hiburan musik Indonesia yaitu karaoke. Adanya tempat karaoke tidak bisa terlepas dari adanya perempuan yang menemaninya menyanyi yang biasa disebut dengan pemandu karaoke atau lebih dikenal sebagai LC (Lady Companion). Fakta awal adanya karaoke dipandang sebagai kegiatan yang identik dengan konotasi negatif. Meski secara formal mereka bukanlah merupakan pelaku prostitusi secara resmi atau terbuka, tetapi dalam praktiknya profesi mereka ini sangat lekat dan identik dengan praktik prostitusi. Metode yang digunakan adalah penelitian kualitatif dengan menggunakan pendekatan interpretatif “pemaknaan” berbasis pada pandangan Foucault dan Giddens. Hasil penelitian ini adalah terdapat relasi antara profesi LC dengan praktik prostitusi dengan tubuh perempuan sebagai alat untuk sarana produksi atau menghasilkan uang dan adanya kekuasaan atas dirinya yang mengontrol akan kebutuhan ekonomi yang sangat mendesak dan akhirnya perempuan LC masuk ke dalam dunia tersebut. Kemudian terjadi pergeseran instruksi sosial terkait makna tubuh dan “kesucian perempuan” sebab hubungan seksual dan virginitas tidak lagi dianggap se-sakral sebelumnya.Kata kunci : Lady Companion (LC), Prostitusi, Makna Tubuh, Kesucian perempuan